Breast lesions with myoepithelial phenotype - KAYA, HANDAN (My University, 2023)
© 2022 John Wiley & Sons Ltd.Myoepithelial cells (MECs) constitute a continuous layer of cells surrounding the breast glands, localised between the epithelial cells (ECs) and the basal membrane. MECs play important roles in normal mammary gland as they produce basal membrane and stimulate secretion. During neoplastic transformation, MECs act as a barrier preventing stromal invasion. MECs themselves can undergo a great variety of changes, ranging from hyperplastic to metaplastic, to neoplastic, and giving rise to a wide spectrum of morphological pictures sometimes difficult to interpret on routine diagnoses. Several benign and malignant breast tumours can present features of MECs differentiation. As these latter tumours are quite infrequent, the purpose of the present study is to offer a review of the morphological spectrum of MECs lesions, with correlations to prognosis.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Surgery Medicine Sciences; Pathology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Yaşam Bilimleri (LIFE); Biyoloji ve Biyokimya; PATOLOJİ; Life Sciences (LIFE); BIOLOGY & BIOCHEMISTRY; PATHOLOGY; Patoloji ve Adli Tıp; Histoloji; Pathology and Forensic Medicine; Histology; breast; epithelial cell; myoepithelial cell; myoepithelial cell differentiation; myoepitheliosis